2003
DOI: 10.1074/jbc.m209570200
|View full text |Cite
|
Sign up to set email alerts
|

MTA1 Interacts with MAT1, a Cyclin-dependent Kinase-activating Kinase Complex Ring Finger Factor, and Regulates Estrogen Receptor Transactivation Functions

Abstract: The transcriptional activity of estrogen receptor-␣ is controlled by coregulators. MTA1 (metastasis-associated protein 1) represses estrogen receptor-␣-driven transcription by recruiting histone deacetylases (HDACs) to the estrogen response element containing target gene chromatin in breast cancer cells. Using a yeast twohybrid screen with the MTA1 C-terminal domain as bait, we identified MAT1 (mé nage á trois 1) as an MTA1-binding protein. MAT1 is an assembly/targeting factor for cyclin-dependent kinase-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 30 publications
1
42
1
Order By: Relevance
“…The augmented expression contributes to enhanced histone deacetylase activity, inhibition of oestrogen-receptor element-driven gene transcription, and progression to an invasive phenotype. Moreover, it has been reported that MAT1 (ménage á trios 1), an assembly/targeting factor for cyclin-dependent kinase-activating kinase (CAK), is an MTA1-binding protein (Talukder et al, 2003). The results reported in the latter study suggest that MTA1 might inhibit CAK-induced oestrogen receptor transactivation function by recruiting histone deactylase.…”
supporting
confidence: 64%
“…The augmented expression contributes to enhanced histone deacetylase activity, inhibition of oestrogen-receptor element-driven gene transcription, and progression to an invasive phenotype. Moreover, it has been reported that MAT1 (ménage á trios 1), an assembly/targeting factor for cyclin-dependent kinase-activating kinase (CAK), is an MTA1-binding protein (Talukder et al, 2003). The results reported in the latter study suggest that MTA1 might inhibit CAK-induced oestrogen receptor transactivation function by recruiting histone deactylase.…”
supporting
confidence: 64%
“…Recruitment of the MTA1⅐HDAC4 Complex on the PTEN Promoter Inhibits PTEN Expression-To understand the molecular mechanism underlying the noted MTA1 repression of PTEN transcription, we carried out a ChIP analysis with HDAC2, a component of the MTA1 corepressor complex (29). However, we failed to detect any recruitment of HDAC2 onto the PTEN promoter (Fig.…”
Section: Mta1 Expression Inversely Correlates With Pten Expresmentioning
confidence: 99%
“…Earlier studies have demonstrated that MTA1 forms a corepressor complex with HDAC1/2 and is recruited to the target gene promoters, thereby repressing gene transcription (29). For example, the MTA1⅐HDAC2 complex was identified as a transcriptional corepressor of number of tumor suppressor genes such as BRAC1, p21WAF1, and RNF144, where the MTA1⅐HDAC2 complex recruits onto their promoters and down-regulates the expression of these genes, leading to accelerated tumor growth and metastasis (32,41,42).…”
Section: Mta1 Expression Inversely Correlates With Pten Expresmentioning
confidence: 99%
“…Recent data suggest that the Ets-2 transcription factor may play a role in the repression of the BRCA1 promoter (Baker et al, 2003). The notion that MTA1 might be a corepressor was merely speculative until the recent discovery that MTA1 associates with histone deacetylases (HDACs) and thereby helps to repress estrogen receptor-a (ERa) transactivation in breast cancer cells (Mazumdar et al, 2001;Talukder et al, 2003). Since the BRCA1 promoter contains an atypical estrogen-responsive element (ERE) (Xu et al, 1997), we hypothesized that MTA1 might play a role in BRCA1 repression.…”
Section: Introductionmentioning
confidence: 99%